Plant responses to ambient temperature fluctuations and water-limiting conditions: A proteome-wide perspective - Johnová, Patricie; Skalák, Jan; Saiz-Fernández, Iñigo; Brzobohatý, Břetislav (Biochimica et biophysica acta, 2016)
BACKGROUND: Every year, environmental stresses such as limited water and nutrient availability, salinity, and temperature fluctuations inflict significant losses on crop yields across the globe. Recently, developments in analytical techniques, e.g. mass spectrometry, have led to great advances towards understanding how plants respond to environmental stresses. These processes are mediated by many molecular pathways and, at least partially, via proteome-environment interactions. SCOPE OF REVIEW: This review focuses on the current state of knowledge about interactions between the plant proteome and the environment, with a special focus on drought and temperature responses of plant proteome dynamics, and subcellular and organ-specific compartmentalization, in Arabidopsis thaliana and crop species. MAJOR CONCLUSIONS: Correct plant development under non-optimal conditions requires complex self-protection mechanisms, many of them common to different abiotic stresses. Proteome analyses of plant responses to temperature and drought stresses have revealed an intriguing interplay of modifications, mainly affecting the photosynthetic machinery, carbohydrate metabolism, and ROS activation and scavenging. Imbalances between transcript-level and protein-level regulation observed during adaptation to abiotic stresses suggest that many of the regulatory processes are controlled at translational and post-translational levels; proteomics is thus essential in revealing important regulatory networks. GENERAL SIGNIFICANCE: Because information from proteomic data extends far beyond what can be deduced from transcriptome analysis, the results of proteome studies have substantially deepened our understanding of stress adaptation in plants; this is clearly a prerequisite for designing strategies to improve the yield and quality of crops grown under unfavorable conditions brought about by ongoing climatic change. This article is part of a Special Issue entitled: Plant Proteomics--a bridge between fundamental processes and crop production, edited by Dr. Hans-Peter Mock.
Keywords: proteiny huseníčku; proteom; Arabidopsis; voda; Acclimatization; Crops, Agricultural; zemědělské plodiny; Stress, Physiological; Water; aklimatizace; Crops; Drought; Cold stress; Plant proteome; fyziologický stres; Proteome; Heat stress; Arabidopsis Proteins